Exploring English Education Student’s Experience in Enhancing English Speaking Skill - Melia, Sindi; Yanto, Elih Sutisna; Kamil, Acep Bahrum (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
English learning should be supported by an interesting and good strategy to make students’ learning valuable, enjoyable, and interested, as well as in a Speaking setting, but the most important thing is a willingness to study. The purpose of the study is to describe the experience faced by one English education student in enhancing English speaking skills after facing offline or face-to-face classes and then suddenly facing online classes because of the covid-19 pandemic attack. This research is using Qualitative approach and Narrative Inquiry as a research design in gaining the data. The participant of this research is one English education student in the eighth semester who has faced offline or face-to-face classes and then suddenly face online classes because of the covid-19 pandemic. The result of this research describes some interesting experiences that the participant has passed to enhance her English speaking skill, such as some habits and strategies that she has been doing and joining competitions, which construct her to become a good English speaker.